Hepatopathy of Mauriac syndrome: a retrospective review from a tertiary liver centre. Issue 4 (10th January 2014) - Fitzpatrick, E; Cotoi, C; Quaglia, A; Sakellariou, S; Ford-Adams, M E; Hadzic, N
Abstract : Background: Mauriac syndrome is characterised by growth failure, cushingoid appearance and hepatomegaly which occurs in patients with insulin dependent diabetes and was first described shortly after the introduction of insulin as a treatment for the condition. Objective: To describe the clinical features, histological findings and outcome of young people with glycogenic hepatopathy, the hepatic manifestation of Mauriac syndrome (MS). Design: Retrospective cohort study. Patients: Young people with glycogenic hepatopathy. Setting: Tertiary paediatric hepatology unit. Results: Thirty-one young people (16 M), median age of 15.1 years (IQR 14–16.2) presented within the study period. Median age of diagnosis of diabetes was 10 years (IQR 8–11). Median insulin requirement was 1.33 units/kg/day; median HbA1c was 96.7 mmol/mol (IQR 84.7–112.0). Growth was impaired: median height z-score was −1.01 (−1.73 to 0.4) and median body mass index (BMI) z-score was 0.28 (−0.12 to 0.67). Hepatomegaly was universal with splenomegaly in 16%. Transaminases were abnormal with a median aspartate aminotransferase (AST) of 76 IU/L and gamma glutamyltransferase of 71 IU/L. Liver biopsy was undertaken in 19 (61%). All showed enlarged hepatocytes with clear cytoplasm with glycogenated nuclei in 17. Steatosis was present in the majority. Inflammation was present in 8 (42%). Fibrosis was seen in 14 (73%) and was generally mild though 2 had bridging fibrosis. Megamitochondria were described in 7. Presence of megamitochondria correlated with AST elevation (p=0.026) and fibrosis on biopsy (p=0.007). At follow-up 17 children had normal or improved transaminases, in 13 there was no change. Transaminases followed the trend of the child's HbA1c. Conclusions: Despite modern insulin regimens and monitoring in children with type 1 diabetes, MS still exists. Significant steatosis, inflammation and fibrosis were all seen in liver biopsies.